Tar Removal From Biomass Producer Gas By Absorption And Adsorption Methods - Ahmad, Nor Azlina (2014)
Tar in biomass producer gas should be removed to avoid blocking of the pipe lines and to allow producer gas utilization in internal combustion engines (ICE) and turbines for power generation. Among the physical tar removal methods, scrubbing technique are more attractive to remove tar from biomass producer gas. This technique aims to use reusable material for tar removal. Tar removal system was conducted by two methods: absorption method (collected waste palm cooking oil (CWPCO), laboratory waste palm cooking oil (LWPCO), diesel oil and water) and combination of absorption method (optimum absorption medium are selected) with adsorption method (commercial activated carbon (CAC), empty fruit bunch char (EFBC) and oil palm shell char (OPSC». Tar species and oil-based mediums (CWPCO, LWPCO and diesel oil) were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Whilst, adsorption medium properties were determined using Thermogravimetric Analyzer (TGA), Microstructure Analysis (BEn and Scanning Electron Microscope (SEM).